ATP1A3-related epilepsy: Report of seven cases and literature-based analysis of treatment response. (February 2020) - Gasser, Marius; Boonsimma, Ponghatai; Netbaramee, Wiracha; Wechapinan, Thanin; Srichomthomg, Chalurmpon; Ittiwut, Chupong; Krenn, Martin; Zimprich, Fritz; Milenkovic, Ivan; Abicht, Angela; Biskup, Saskia; Roser, Timo; et al.
Highlights: ATP1A3 gene is related to difficult-to-treat epilepsy. Information on anti-epileptic drug (AED) treatment is rare. Most used AEDs: levetiracetam, phenobarbital, valproic acid and topiramate. No most effective AED; and 45% of patients did not show any seizure relief. Median onset of symptoms was 2 months of age. Abstract: ATP1A3 related disease is a clinically heterogeneous condition currently classified as alternating hemiplegia of childhood, rapid-onset dystonia-parkinsonism and cerebellar ataxia, areflexia, pes cavus, optic atrophy, and sensorineural hearing loss. Recently, it has become apparent that a remarkably large subgroup is suffering from often difficult-to-treat epilepsy. The aim of the present study was to assess the prevalence and efficacy of commonly used anti-epileptic-drugs (AEDs) in patients with ATP1A3 r elated seizures. Therefore, we performed a retrospective study of patients in combination with a systematic literature-based review. Inclusion criteria were: verified ATP1A3 mutation, seizures and information about AED treatment. The literature review yielded records for 188 epileptic ATP1A3 patients. For 14/188 cases, information about anti-epileptic treatment was available. Combined with seven unpublished records of ATP1A 3 patients, a sample size of 21 patients was reached. Most used AED were levetiracetam (n = 9), phenobarbital (n = 8), valproic acid (n = 7), and topiramate (n = 5). Seizure reduction was reported for 57% of patients (n = 12). No individual AEDs used (either alone or combined) had a success rate over 50%. There was no significant difference in the response rate between various AEDs. Ketogenic diet was effective in 2/4 patients. 43% of patients (n = 9) did not show any seizure relief. Even though Epilepsy is a significant clinical issue in ATP1A3 patients, only a minority of publications provide any information about patients' anti-epileptic treatment. The findings of treatment effectiveness in only 57% (or lower) of patients, and the non-existence of a clear first-line AED in ATP1A3 related epilepsy stresses the need for further research.